2017
DOI: 10.3389/fpsyg.2017.00283
|View full text |Cite
|
Sign up to set email alerts
|

Attainable and Relevant Moral Exemplars Are More Effective than Extraordinary Exemplars in Promoting Voluntary Service Engagement

Abstract: The present study aimed to develop effective moral educational interventions based on social psychology by using stories of moral exemplars. We tested whether motivation to engage in voluntary service as a form of moral behavior was better promoted by attainable and relevant exemplars or by unattainable and irrelevant exemplars. First, experiment 1, conducted in a lab, showed that stories of attainable exemplars more effectively promoted voluntary service activity engagement among undergraduate students compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(174 citation statements)
references
References 96 publications
6
166
0
2
Order By: Relevance
“…The same variable was surveyed once again twelve weeks after the pre-test survey period. Han et al (2017) reported that the post-test service engagement in the peer exemplar group was greater than that in the historic figure group after controlling for the pre-test service engagement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same variable was surveyed once again twelve weeks after the pre-test survey period. Han et al (2017) reported that the post-test service engagement in the peer exemplar group was greater than that in the historic figure group after controlling for the pre-test service engagement.…”
Section: Methodsmentioning
confidence: 99%
“…The original findings, which resulted from classical statistical analyses, were reported in Study 2 in Han, Kim, Jeong and Cohen (2017). In this study, the students participated in two different types of moral educational intervention activities for eight weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Often, all it takes is one person to serve as an exemplar for others to follow suit (Han et al. ). A single household can help inspire neighbors, friends, colleagues, and extended family.…”
Section: Toward An Ascetic Antiracismmentioning
confidence: 99%
“…Here is one concrete example that demonstrates how neuroscience of morality can provide moral education with useful heuristics about how to develop a more effective educational program. Han, Kim, Jeong, and Cohen's (2017) moral education program that utilized the stories of moral exemplars was initially inspired by studies in neuroscience of morality that examined the involvement of self-related processes in the moderation of moral emotion and motivation. A meta-analysis of previous moral psychological neuroimaging studies (Han, 2017) and a functional neuroimaging experiment (Han et al, 2016) showed significant associations among self-related brain regions and morality-related brain regions.…”
Section: Rethink How To Learn From Neuroscience Of Morality To Improvmentioning
confidence: 99%
“…A meta-analysis of previous moral psychological neuroimaging studies (Han, 2017) and a functional neuroimaging experiment (Han et al, 2016) showed significant associations among self-related brain regions and morality-related brain regions. Based on these findings, Han et al (2017) designed and tested an exemplar-applied moral education program that used close-other exemplars (e.g., friends, family members) that might have stronger psychological connectivity with students; their study reported that the aforementioned program inspired by neuroscience significantly promoted students' moral motivation. Han et al (2017) attempted to directly focus on activity in specific brain regions after reviewing localization studies.…”
Section: Rethink How To Learn From Neuroscience Of Morality To Improvmentioning
confidence: 99%